The Effect of Personality Traits on the Life Satisfaction of the Medical Teachers - Dr. Sajid Mahmood Alvi; Dr. Mazhar Iqbal Bhatti; Ayla Khan (Journal of Management Practices, Humanities and Social Sciences, 2022)
The present study was conducted to examine the effect of personality traits on the life satisfaction of medical teachers. The cross-sectional research design was used to collect data. Data were collected by purposive sampling technique from the medical teachers of Ayyub Medical College, Women Medical College Abbottabad, International Medical College Abbottabad, Frontier Institute of Medical Sciences Haripur, and Abbottabad of Hazara Division KPK. The total sample size of this study was 200 medical teachers. 50% of the data were collected from males and 50% from females hence there was a 100% response rate. The big five personality scale and life satisfaction scale with greater than 0.70 alpha reliability coefficients were self administered by authors and analyzed using SPSS 20 version. The authors personally approached the research participants for data collection. Analysis shows that the personality traits extraversion, conscientiousness, openness to change, and agreeableness are positively related to life satisfaction while neuroticism is negatively related to life satisfaction. This study ensures that personality traits play an important role in depicting the life satisfaction of medical teachers.